Differential effects of high-frequency transcranial random noise stimulation (hf-tRNS) on contrast sensitivity and visual acuity when combined with a short perceptual training in adults with amblyopia. (June 2018) - Moret, Beatrice; Camilleri, Rebecca; Pavan, Andrea; Lo Giudice, Giuseppe; Veronese, Antonella; Rizzo, Roberta; Campana, Gianluca
Abstract: Amblyopia is a neuro-developmental disorder characterised by several functional impairments in spatial vision even with the best optical correction. There is evidence that extensive perceptual training can improve visual acuity (VA) and contrast sensitivity (CS) in adults with amblyopia. In the present study, we assessed the efficacy of a recently developed neuro-modulatory technique (i.e., high-frequency transcranial random noise stimulation; hf-tRNS) combined with a short perceptual training in adults with amblyopia. One group of ten participants underwent a short (8 sessions) monocular training in a contrast detection task with concurrent hf-tRNS, whereas another group of ten participants underwent the same training protocol but with Sham stimulation (control group). The training consisted of a two-interval forced choice (2IFC) contrast detection task in which participants had to detect the presence of a central Gabor patch flanked by two high-contrast collinear Gabors (lateral masking). The results showed a significant and similar improvement of CS for both groups, suggesting that hf-tRNS is not crucial for the improvement of CS. However, for VA, a significant improvement was only observed in the hf-tRNS group with a mean VA improvement of 0.19 LogMAR in the amblyopic eye. Most notably, this improvement was achieved after eight training sessions. The results are discussed in terms of the influence of hf-tRNS on short-term neural plasticity. Highlights: Perceptual training improves visual functions in adults with amblyopia. With a short training we improved contrast sensitivity in adults with amblyopia. When the training was coupled with hf-tRNS improvement transferred to visual acuity. No transfer to visual acuity was observed with Sham stimulation. hf-tRNS might boost transfer of perceptual learning to untrained visual functions.